Antibody delivery of drugs and radionuclides: factors influencing clinical pharmacology. (June 2011) - Prabhu, Saileta; Boswell, C Andrew; Leipold, Douglas; Khawli, Leslie A; Li, Dongwei; Lu, Dan; Theil, Frank-Peter; Joshi, Amita; Lum, Bert L
The therapeutic rationale of antibody conjugates is the selective delivery of a cytotoxin to tumor cells via binding and internalization of the monoclonal antibodies to a specific cell-surface antigen, thereby enhancing the therapeutic index of the cytotoxin. The key structural and functional components of an antibody conjugate are the antibody, the linker and the cytotoxin (chemical or radionuclide) with each component being critical for the successful development of the conjugate. Considerable efforts have been made in understanding the pharmacokinetics, pharmacodynamics, tissue distribution, metabolism and pharmacologic effects of these complex macromolecular entities. The purpose of this article is to discuss the properties and various structural components of antibody conjugates that influence their clinical pharmacology.